John Peradotto. Man in the Middle Voice. Name and Narration in the Odyssey, Princeton-New Jersey, Princeton University Press, 1990, xi + 193 pp. - Zecchin de Fasano, Graciela Cristina (1994)
Fil: Zecchin de Fasano, Graciela Cristina. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.